2017
DOI: 10.21884/ijmter.2017.4288.h0fca
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Properties of Aerospace Materials Through Additive Manufacturing

Abstract: Abstract-Additive Manufacturing (AM) process has been effective in producing materials that are being utilized by the aerospace industry in order to improve their performance by increasing their properties. Industry now opts for this technique over conventional methods as it has enormous advantages and applications. This Additive Manufacturing process is capable of producing complex near net shape of parts. The materials that are produced by this technique for aerospace industries are metal alloys, metal matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Casati et al [27] reported reduced tensile strength with a wide scatter in the elongation to failure in LPBF AISI 316L stainless steel (316L SS) and attributed this to the presence of partially melted powder particles in the microstructure. AM components can also exhibit certain variations in mechanical and microstructural properties between different machines using the same set up, and even among the same parts printed in the same batch on the same platform [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Casati et al [27] reported reduced tensile strength with a wide scatter in the elongation to failure in LPBF AISI 316L stainless steel (316L SS) and attributed this to the presence of partially melted powder particles in the microstructure. AM components can also exhibit certain variations in mechanical and microstructural properties between different machines using the same set up, and even among the same parts printed in the same batch on the same platform [28,29].…”
Section: Introductionmentioning
confidence: 99%